A Rare Inherited 15q11.2-q13.1 Interstitial Duplication with Maternal Somatic Mosaicism, Renal Carcinoma, and Autism - Urraca, Nora; Potter, Brian; Hundley, Rachel; Pivnick, Eniko K.; McVicar, Kathryn; Thibert, Ronald L.; Ledbetter, Christopher; Chamberlain, Reed; Miravalle, Leticia; Sirois, Carissa L.; Chamberlain, Stormy; Reiter, Lawrence T. (Frontiers in Genetics, 2016)
Chromosome 15q11-q13.1 duplication is a common copy number variant associated with autism spectrum disorder (ASD). Most cases are de novo, maternal in origin and fully penetrant for ASD. Here we describe a unique family with an interstitial 15q11.2-q13.1 maternal duplication and the presence of somatic mosaicism in the mother. She is typically functioning, but formal autism testing showed mild ASD. She had several congenital anomalies, and she is the first 15q Duplication case reported in the literature to develop unilateral renal carcinoma. Her two affected children share some of these clinical characteristics, and have severe ASD. Several tissues in the mother, including blood, skin, a kidney tumor, and normal kidney margin tissues were studied for the presence of the 15q11-q13.1 duplication. We show the mother has somatic mosaicism for the duplication in several tissues to varying degrees. A growth competition assay in two types of stem cells from duplication 15q individuals was also performed. Our results suggest that the presence of this interstitial duplication 15q chromosome may confer a previously unknown growth advantage in this particular individual, but not in the general interstitial duplication 15q population.